Surface diffusion of dysprosium on the W(1 1 1) facet - Biernat, T.; Błaszczyszyn, R. (Applied surface science, 2004)
Diffusion of dysprosium on the (1 1 1) facet of a tungsten micromonocrystal was investigated by means of spectral analysis of field emission current fluctuations. The experimental spectral density functions of the current fluctuations were analysed by using Gesley and Swanson’s theoretical spectral density function, which enables to determine the surface diffusion coefficient D for dysprosium. Derived from the temperature dependence of D, the diffusion activation energy E is presented for some Dy coverages θ (1 1 1) . In the temperature range 400–600 K, the E first drops from 1.25 eV per atom at θ (1 1 1) ≈0.25 ML to 0.48 eV per atom at θ (1 1 1) ≈1 ML (corresponding to the minimum of the work function of the system), then increases to 1.03 eV per atom at θ (1 1 1) ≈1.3 ML. The results are discussed from the aspects of the substrate structure and interaction in the adsorbed layer.